The role of the Judiciary in applicability of fundamental rights (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The purpose of this article is to examine which role the Judiciary must play in the implementation of the so-called fundamental rights of second class – those dependents of positive actions from the State. An empirical analysis of the social reality is enough to indicate that many individuals are kept in extremely poor conditions and difficult access to vital items of daily life, for which the Constitution recognizes several rights. In this context, the Judiciary is implementing such rights. This controversial endeavor must be delimited in order to function in accordance with the Constitution. This paper seeks to demonstrate that the Judiciary cannot intervene in all decision-making spheres of the State on the pretext of implementing fundamental rights of second class. On the other hand, it is also clear that the political entities of the federation (Federal Government, the States, the Federal District and the Municipalities) cannot use the default argument of the “under reserve of possibilities” in order to avoid the implementation of the social rights which such entities are in charge of.
Keywords: fundamental rights; Judiciary; judicial activism; under reserve of possibilities; economic social and cultural rights